Separate roles for state and trait anxiety in the formation of shu syndrome: testing a moderated mediation hypothesis - Walter, Glenn D. (The prison journal, 2022)
It has been proposed that state anxiety, aroused when an inmate is initially placed in restrictive housing, interacts with the sequestering Special Housing Unit (SHU) environment to overtax the individual's already limited coping resources, and promotes later emotional problems and psychological deterioration. This study tested a SHU syndrome hypothesis with a moderated mediation path analysis of 69 male inmates. Results revealed that group status (general population vs. restrictive housing) interacted with state anxiety to increase trait anxiety and ineffective coping, which then gave rise to higher staff ratings of psychological disturbance in inmates with no prior history of mental illness